2017
DOI: 10.1039/c7ra01238a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of magnetic core–shell Fe3O4@TiO2 nanoparticles from electric arc furnace dust for photocatalytic degradation of steel mill wastewater

Abstract: The study was undertaken to design magnetic core-shell Fe 3 O 4 @TiO 2 nanoparticles from electric arc furnace dust and evaluate its photocatalytic activity on organic pollutant degradation from steel industry wastewater.Different molar ratios of Fe 3 O 4 to TiO 2 were tested on Fe 3 O 4 @TiO 2 nanoparticles. The materials were characterized using X-ray diffraction, X-ray photoelectron spectroscopy, Fourier transform-infrared spectroscopy, scanning electron microscopy, energy-dispersive X-ray spectroscopy, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 114 publications
(35 citation statements)
references
References 41 publications
1
34
0
Order By: Relevance
“…According to the TEM image of core-interlayer-shell Fe 3 O 4 /SiO 2 /TiO 2 nanoparticle the dark and bright regions correspond to the Fe 3 O 4 and the shell, respectively. The magnetic core is identified as the darker region compared to the non-magnetic SiO 2 and TiO 2 shell area due to their different electron-absorbing abilities [28]. The core-interlayer-shell structure of Fe 3 O 4 coated with SiO 2 and TiO 2 was confirmed by EDXS mapping, presented in Figure 5b.…”
Section: Characterization Of the Nanoparticlesmentioning
confidence: 64%
See 3 more Smart Citations
“…According to the TEM image of core-interlayer-shell Fe 3 O 4 /SiO 2 /TiO 2 nanoparticle the dark and bright regions correspond to the Fe 3 O 4 and the shell, respectively. The magnetic core is identified as the darker region compared to the non-magnetic SiO 2 and TiO 2 shell area due to their different electron-absorbing abilities [28]. The core-interlayer-shell structure of Fe 3 O 4 coated with SiO 2 and TiO 2 was confirmed by EDXS mapping, presented in Figure 5b.…”
Section: Characterization Of the Nanoparticlesmentioning
confidence: 64%
“…Therefore, the lower photocatalytic activity of BaFe 12 O 19 /SiO 2 /TiO 2 _2 nanocomposite results from the properties of the photocatalytic layer instead of the magnetic core behavior. Salamat et al [28] reported that the variations in the photocatalytic activity of TiO 2 /SiO 2 deposited on Fe 3 O 4 are related to the effect of change in the molar ratio of Ti and Si to Fe 3 O 4 . Therefore, it can be assumed that the amount of silica and titania deposited on the surface of the ferrite core should be determined depending on the ferrite core particles size and shape.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, magnetic titania has gained increasing attention, as it has the advantages of magnetic recovery and excellent photocatalytic properties [15,16,17,18,19]. They can achieve the fast separation and easy recovery of nano-TiO 2 by external magnetic fields, thus preventing the loss of active components and improving the durability of catalysts.…”
Section: Introductionmentioning
confidence: 99%